Dialogues between education, art and cultural policy in Brazil (Revista Contexto & Educação, 2026)
The intersection between art and education permeates cultural policy in Brazil, so that educational actions are configured as a current phenomenon in cultural institutions. In this paper, we aim to reflect on the interrelationships between fruition and pedagogical action in cultural policy through a bibliographic research that mobilizes both authors in the field of cultural policies as well as those who reflect on the overlaps between art and education. To this end, we approach the notion of cultural policy to highlight the links between educational actions and artistic events. Through examples of exhibitions and educational actions, such as the Bienal de São Paulo, the Bienal do Mercosul and initiatives such as the lecture-performance by Grada Kilomba, we discuss the sensitive evocation of certain educational actions, as well as the pedagogical concern of certain exhibitions. We realized, in our conclusions, that cultural policy in Brazil has a history of comings and goings of confluences between pedagogical action and the promotion of aesthetic experiences present in artistic projects. The examples discussed allowed us to show that formative processes can act as part of the public's aesthetic experience. We also emphasize the need for a critical look at the presence of pedagogical actions in the variety of cultural projects proposed by different bodies such as public authorities and private institutions.
Keywords: Education; Aesthetic experience; Cultural policy